Computational insights into Sitahe (Leuconotis eugenifolia) bioactive compounds: A promising approach for radioprotection through p53 inhibition - Dian Pribadi Perkasa; Iin Kurnia; Taufik Muhammad Fakih; Teja Kisnanto; Dwi Ramadhani; Harry Nugroho Eko Surniyantoro; Boky Jeanne Tuasikal; Alfian Mahardika Forentin; Mukh Syaifudin (Pharmacia)
The radioprotective potential of Sitahe (Leuconotis eugenifolia) phytochemicals in cancer radiotherapy remains largely unexplored. In this study, in silico docking simulations were conducted to systematically assess the ability of key phytochemicals from Sitahe to modulate p53 activity, a critical gene in DNA repair and cancer therapy. SwissADME analysis revealed favorable physicochemical properties for compounds such as baurenol, alpha amyrin, and beta amyrin, although high lipophilicity may pose challenges for bioavailability. Molecular docking studies identified strong binding affinities between these compounds and the p53 DNA binding domain, with baurenol demonstrating the highest binding affinity at −6.75 kcal/mol, which is better compared to rhazinilam (−4.55 kcal/mol), leuconolam (−4.36 kcal/mol), leuconoxine (−4.26 kcal/mol), and dehydroleuconoxine (−4.76 kcal/mol). Hydrogen bonding with key residues such as Thr123 further enhanced the stability of these complexes. The low inhibition constants (Ki) suggest significant inhibitory potential, particularly for baurenol (11.31 μM). To evaluate the stability and reliability of these interactions, molecular dynamics (MD) simulations were performed over a duration of 500 ns. The results demonstrated that the selected compounds maintained stable molecular dynamics profiles, showing consistent interactions with the target protein throughout the simulation period. Among the compounds tested, baurenol exhibited the best performance with a MM/PBSA binding energy of −68.568 kJ/mol, which is better than rhazinilam (−63.538 kJ/mol). These findings suggest that baurenol, along with other Sitahe phytochemicals, could serve as dual-function agents, offering protection to healthy tissues from radiation-induced damage while targeting cancer cells through p53 modulation. Although these in silico and MD results are promising, further validation through in vitro and in vivo studies is essential to confirm their therapeutic potential and optimize their pharmacokinetic properties. This study positions Sitahe phytochemicals, particularly baurenol, as promising candidates for the development of novel radioprotective agents in cancer treatment.